Real-Time Imaging of Rabbit Retina with Retinal Degeneration by Using Spectral-Domain Optical Coherence Tomography - Muraoka, Yuki; Ikeda, Hanako Ohashi; Nakano, Noriko; Hangai, Masanori; Toda, Yoshinobu; Okamoto-Furuta, Keiko; Kohda, Haruyasu; Kondo, Mineo; Terasaki, Hiroko; Kakizuka, Akira; Yoshimura, Nagahisa (PLOS ONE, 2012)
Background Recently, a transgenic rabbit with rhodopsin Pro 347 Leu mutation was generated as a model of retinitis pigmentosa (RP), which is characterized by a gradual loss of vision due to photoreceptor degeneration. The purpose of the current study is to noninvasively visualize and assess time-dependent changes in the retinal structures of a rabbit model of retinal degeneration by using speckle noise-reduced spectral-domain optical coherence tomography (SD-OCT). Methodology/Principal Findings Wild type (WT) and RP rabbits (aged 4–20 weeks) were investigated using SD-OCT. The total retinal thickness in RP rabbits decreased with age. The thickness of the outer nuclear layer (ONL) and between the external limiting membrane and Bruch's membrane (ELM–BM) were reduced in RP rabbits around the visual streak, compared to WT rabbits even at 4 weeks of age, and the differences increased with age. However, inner nuclear layer (INL) thickness in RP rabbits did not differ from that of WT during the observation period. The ganglion cell complex (GCC) thickness in RP rabbits increased near the optic nerve head but not around the visual streak in the later stages of the observation period. Hyper-reflective change was widely observed in the inner segments (IS) and outer segments (OS) of the photoreceptors in the OCT images of RP rabbits. Ultrastructural findings in RP retinas included the appearance of small rhodopsin-containing vesicles scattered in the extracellular space around the photoreceptors. Conclusions/Significance In the current study, SD-OCT provided the pattern of photoreceptor degeneration in RP rabbits and the longitudinal changes in each retinal layer through the evaluation of identical areas over time. The time-dependent changes in the retinal structure of RP rabbits showed regional and time-stage variations. In vivo imaging of RP rabbit retinas by using SD-OCT is a powerful method for characterizing disease dynamics and for assessing the therapeutic effects of experimental interventions.